(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تتحدث هذه الدراسة عن عملية المقارنة بين العقود التجارية من وجهة نظر المشتري, أو المستورد ( في حالة التجارة الخارجية ) . حيث أن المشتري ( أو المستورد ) يسعى دوماً نحو اختيار البديل ذي السعر الأدنى ، ولكن بما أن أغلب عمليات الشراء, أو الاستيراد تتم عن طريق القروض التجارية, أو المصرفية ، وشروط هذه القروض تختلف من حالة إلى أخرى ، فإننا سوف نحاول هنا, أن نقارن بين العقود التجارية من وجهة نظر المشتري, وذلك من خلال مقارنة القيم الحالية لهذه العقود المختلفة, واختيار العقد ( أو البديل ) ذي القيمة الحالية الأقل (مفترضين مسبقاً أن المشتري يوافق على باقي شروط العقد القانونية, والإدارية, والفنية .... إلخ). وفي حال عدم ذكر أحد البنود ( المتغيرات ) لواحد من العقود كالسعر, أو معدل الفائدة ، فسوف نبحث في عملية تحديد حد أعلى لهذا المتغير ( البند غير المحدد ), حتى يكون هذا العقد, أو البديل منافساً لغيره من البدائل . This Study is about the process of comparison between the commercial contracts according to the buyer or importer ‘s point of view ( in the case of external trade ) . Whereas the buyer or the importer always seeks to choose the substitute which has less price, but because the most processes of buying or importing are completely through the commercial or bank loans, and the conditions of these loans differ from case to case ,so we will try to compare between the commercial contracts according to the buyer’s point of view by comparing the current prices of these different contracts and choosing the contract or the substitute which has the less current price ( we have already to suppose that the buyer agrees to the rest legal, executive and technical conditions of the contract ) . And if one of the items ( new conditions ) of a contract as the price .Or the interest rate is not mentioned, then we will determine a higher limit for this new condition ( the unlimited item ) till this contract or substitute becomes competitor to the other substitutes.